S100A1 is released from ischemic cardiomyocytes and signals myocardial damage via Toll-like receptor 4 - Rohde, David; Schön, Christoph; Börries, Melanie; Didrihsone, Ieva; Ritterhoff, Julia; Hieke-Kubatzky, Katharina; Völkers, Mirko; Herzog, Nicole; Mähler, Mona; Tsoporis, James N; Parker, Thomas G; Linke, Björn; et al. (EMBO molecular medicine, 2014)
Abstract Members of the S100 protein family have been reported to function as endogenous danger signals (alarmins) playing an active role in tissue inflammation and repair when released from necrotic cells. Here, we investigated the role of S100A1, the S100 isoform with highest abundance in cardiomyocytes, when released from damaged cardiomyocytes during myocardial infarction (MI). Patients with acute MI showed significantly increased S100A1 serum levels. Experimental MI in mice induced comparable S100A1 release. S100A1 internalization was observed in cardiac fibroblasts (CFs) adjacent to damaged cardiomyocytes. In vitro analyses revealed exclusive S100A1 endocytosis by CFs, followed by Toll-like receptor 4 (TLR4)-dependent activation of MAP kinases and NF-?B. CFs exposed to S100A1 assumed an immunomodulatory and anti-fibrotic phenotype characterized i.e. by enhanced intercellular adhesion molecule-1 (ICAM1) and decreased collagen levels. In mice, intracardiac S100A1 injection recapitulated these transcriptional changes. Moreover, antibody-mediated neutralization of S100A1 enlarged infarct size and worsened left ventricular functional performance post-MI. Our study demonstrates alarmin properties for S100A1 from necrotic cardiomyocytes. However, the potentially beneficial role of extracellular S100A1 in MI-related inflammation and repair warrants further investigation.